PENGARUH MEDIA VIDEO ANIMASI TERHADAP PERBENDAHARAAN KOSAKATA BAHASA INGGRIS ANAK USIA DINI USIA 5-6 - Nurjanah, Siti; Rosyidah, Yuni Rahmawati; Harliana, Harliana (CENDEKIA PENDIDIKAN, 2026)
This study aims to determine the effect of using animated videos as a learning medium on increasing English vocabulary in children aged 5–6 years at Maple Tree School. This study used a quantitative approach with an experimental design involving two groups, namely the experimental group and the control group, each consisting of 15 children. The experimental group was given treatment in the form of learning using animated videos tailored to the theme, while the control group used conventional media such as pictures and question and answer methods. The pretest results showed that the initial abilities of the two groups were relatively the same, with an average of 45.33 in the experimental group and 44.67 in the control group. After six meetings, the posttest results showed a higher increase in the experimental group with an average of 83.33 compared to the control group of 66.00. Normality and homogeneity tests showed that the data were normally distributed and homogeneous. The t-test results showed a calculated t value of 6.527 greater than the t-table of 2.048 at a significance level of 0.05, so H0 was rejected and H1 was accepted. Thus, the use of animated videos significantly improves the English vocabulary of children aged 5–6 years.